Decision Support System for Elective Course Selection Using the TOPSIS Method - Ari Rahayu (Journal of Intelligent Decision Support System (IDSS), 2020)
The Information Systems Study Program, Faculty of Da'wah and Communication, UIN Raden Fatah Palembang, is one of the study programs that offers elective courses in the high semester, namely between semesters six and seven with various advantages, making it difficult for students to make choices according to their interests and talents. In line with that, more and more elective courses are being offered as alternative choices. They are Geographic Information System (GIS), Advanced IS Analysis and Design, Data Mining and Warehouse, as well as Sillation Modeling in even semesters and Decision Support Systems, Multitier, Mobile Programming, and Artificial Intelligence as alternatives that the Study Program offers in odd semesters. In connection with this problem, Then a Decision Support System for the Selection of Elective Courses is designed so that students can determine the choice of elective courses appropriately according to their interests and talents. The method used for the Elective Course Selection Decision Support System is the Technique Order Preference by Similarity To Ideal Solution (TOPSIS) method. This method was chosen because it is able to choose the best alternative from a number of alternatives, in this case the alternative in question is the best choice of courses based on the specified criteria. The results of the process of implementing the TOPSIS method can sort alternatives from the largest value to the smallest value, so that elective courses are produced as solutions and suggestions for decision making for students